2020
DOI: 10.1037/pag0000464
|View full text |Cite
|
Sign up to set email alerts
|

20-year trajectories of health in midlife and old age: Contrasting the impact of personality and attitudes toward own aging.

Abstract: Personality traits affect health throughout adulthood. Recent research has demonstrated that attitudes toward own aging (ATOA) also play an important role in various health outcomes. To date, the role of personality versus ATOA for health has rarely been considered in parallel and contrasted for different periods of the second half of life, such as midlife versus early old age. We posit that with advancing age, associations of personality and ATOA with trajectories of health might change. To address this assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 129 publications
2
11
0
Order By: Relevance
“…In April 2020, however, the mean SA in the sample was already older again. In another study (Wettstein & Wahl, 2021a), a similar trend was found, with individuals assessed on days with more reported COVID infections reporting a younger subjective age than those assessed on days with fewer infections. Subjective age seems to fluctuate on a microlongitudinal time level (see also Bellingtier et al, 2017; Kornadt et al, 2021; Kotter-Grühn et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
“…In April 2020, however, the mean SA in the sample was already older again. In another study (Wettstein & Wahl, 2021a), a similar trend was found, with individuals assessed on days with more reported COVID infections reporting a younger subjective age than those assessed on days with fewer infections. Subjective age seems to fluctuate on a microlongitudinal time level (see also Bellingtier et al, 2017; Kornadt et al, 2021; Kotter-Grühn et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
“…Their study found that more positive SPA predicted better physical functioning (rather than the reverse) 2 years later and, additionally, found that self-efficacy mediated this relationship, providing a link between the beliefs of positive SPA to improved physical functioning (Tovel et al, 2019). Wettstein et al (2020) proposed that personality factors, namely neuroticism and conscientiousness, may be involved in the relationship. Their study involved two cohorts: middle-aged adults (43–46 years) and older adults (61–64 years).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we will focus on two of the Big Five traits, namely neuroticism and extraversion. Whereas, higher neuroticism is associated with worse health outcomes, such as poorer self-rated (83)(84)(85) or physician-rated health (86,87), associations of extraversion with health outcomes are positive (88)(89)(90).…”
Section: The Role Of Personality For Pain In Advanced Old Agementioning
confidence: 99%